Flexibility of Reconfiguration of Employment Rules in Factory Operations as a Hibernation Mode of Business Life at PT CBP Company in the COVID-19 Pandemic Season - Aesah, Siti; Sutarno, Sutarno; Mogi, Agustina (Adpebi Science Series, 2022)
The worldwide impact of the COVID-19 pandemic has forced every business entity to act flexibly to accept the blow of this storm. Regulations in the Manpower Law according to Law No. 13 of 2003 and its transition to the CIPTAKER Law of 2021 are not fully enforceable. It takes some acrobatics in the field of manpower management and work operations to prolong the life of a business entity. At least until the time when this pandemic passes and things return to normal. This state is similar to a hibernation state where all expenses are minimized and energy is only used to survive. This study examines the types of acrobatics that are carried out and standardized as products of intermediary regulations during the pandemic season published by the company as a rescue measure to prolong the life of the business. The objectives of this research are: First, to create a strategy of Flexibility Reconfiguration of Employment Rules in Factory Operations. Second, implementing and testing the Business Life Hibernation Mode at PT CBP Company whether it can be used as a strategy to save yourself from the Covid-19 pandemic storm. From the results of the factor analysis, the results of the analysis of three groups of components were found. The first component is Visionary Creative factors, Asset Identification, Online Content, Loyal Customers. The second component is the factors of business continuity, Marketing Strategy. The third component is the factors of Procurement Efficiency, Crisis Sensitivity, Flexibility of Plans, Market Targeting, Product Security, Promotional Media, Marketing Relevance.